Proceedings of the Great Lakes Symposium on VLSI 2012
DOI: 10.1145/2206781.2206795
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the power delivery wall using voltage stacking

Abstract: We propose the use of voltage stacking for addressing some of the power delivery issues for many-core processors. To demonstrate the effectiveness of our method we first design a proxy for a many-core stacked processor in the form of a regular structure using multiple ring oscillators where we can control the voltage, frequency and switching activity for individual rings. For intermediate voltage rail regulation, we propose a push pull-based switched capacitor regulator designed specifically for balancing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…In response to the power delivery challenge caused by excessive current consumption, various research proposals [1][2][3][4] explored the idea of using a charge-recycled power delivery structure to support 3D-IC. Charge-recycling, or voltage-stacking (V-S), refers to power delivery that ar ranges multiple circuit blocks electrically in series.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the power delivery challenge caused by excessive current consumption, various research proposals [1][2][3][4] explored the idea of using a charge-recycled power delivery structure to support 3D-IC. Charge-recycling, or voltage-stacking (V-S), refers to power delivery that ar ranges multiple circuit blocks electrically in series.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, explicit voltage regulation is required in V-S PDNs to compensate for the current-consumption mismatch between layers, and regulate voltages at the in ternal nodes. Based on circuit-level implementations and tests, prior research proposals have demonstrated the fea sibility of using these explicit regulators in V-S PDNs [2,4]. However, the trade-off in voltage noise between V-S PDNs and traditional PDNs is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…With this internal recycling, for almost the same power consumption, the current drawn through the supply will be reduced to 1/n of conventional parallel loads (n is the number of cores stacked) [5][6][7]. This will also reduce the off-chip I 2 R power loss by a factor of n 2 and IR drop by a factor of n. The efficiency of this technique depends on the current mismatch among the stacked domains.…”
Section: Voltage Stacking Ideamentioning
confidence: 99%
“…By using a SC regulator, the achievable efficiency can be more than LDO. This idea is an extension of our work on GALS-based stacked cores which allow the intermediate node to implicitly track the workload of the different cores [5].…”
Section: Dc-dc Conversion Using Voltage Stackingmentioning
confidence: 99%
See 1 more Smart Citation